EFFECTIVENESS OF USING CANVA INTERACTIVE MEDIA ON FLAT BUILDINGS MATERIAL IN CLASS III SDN CIJANTUNG 01 - Susanti, Sri (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to analyze the effectiveness of using interactive learning media Canva in improving the learning outcomes of third-grade students at SDN Cijantung 01 on the topic of two-dimensional shapes. Method: The method used is Classroom Action Research (CAR) conducted in two cycles. Data were collected through observation, learning achievement tests, and student response questionnaires. Result: The results showed that Canva media increased student engagement, clarified the material, and made the learning process more enjoyable. The average student score increased from 66 before the cycles to 81 at the end of the second cycle. Novelty: This proves that Canva interactive media is effective for teaching mathematics in elementary schools, offering a modern, student-centered approach that enhances both understanding and enthusiasm in mathematical learning.